2019
DOI: 10.3390/ijerph16152709
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Controlling Behaviors of Physical Education Teachers and Objectively Measured Leisure-Time Physical Activity in Adolescents

Abstract: The facilitative role of perceived autonomy support from physical education (PE) teachers on adolescents’ leisure-time physical activity (PA) has been supported. This study aimed to examine the mechanism by which perceived controlling behaviors from PE teachers relate to adolescents’ objectively measured leisure-time PA. In a three-wave prospective study, a total of 159 students (64 boys) aged 11 to 19 years old (Mage = 14.94 years; SD = 2.11) completed measures of perceived controlling behavior, frustration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
31
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 61 publications
(125 reference statements)
8
31
2
1
Order By: Relevance
“…Each subscale comprised five items with responses provided on seven-point scales ranging from 1 (strongly disagree) to 7 (strongly agree). Previous research has supported the reliability and factor structure of the current measure (Tilga et al, 2019).…”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations
“…Each subscale comprised five items with responses provided on seven-point scales ranging from 1 (strongly disagree) to 7 (strongly agree). Previous research has supported the reliability and factor structure of the current measure (Tilga et al, 2019).…”
Section: Methodsmentioning
confidence: 62%
“…Available in: https://doi.org/10.17605/OSF.IO/3EMAV 4 behaviour from PE teachers is related via thwarting of psychological needs and external regulation to adolescents' objective MVPA (Koka et al, 2019). However, the amount of the variance in objective PA explained by motivational correlates in these studies was relatively low, ranging between 6% (Kalajas- Tilga et al, 2019) and 14% (Koka et al, 2019), suggesting that other possible factors determining PA have not been measured. Previous research has suggested that it might be perceived effort that is associated with students' motivational regulations and physical activity (e.g., Hagger et al, 2005;Ntoumanis, 2001;Standage et al, 2003).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Los profesores manifiestan un comportamiento de control cuando ignoran las perspectivas de los estudiantes, comportándose de manera autoritaria e imponiendo una forma específica y preconcebida de pensar, sentir y comportarse. Este estilo de enseñanza, presiona a los estudiantes a adherirse a los valores del profesor y por tanto, pueden usarse para imponer disciplina y asegurar el cumplimiento del estudiante (Bartholomew et al, 2018;Haerens et al, 2015;Koka et al, 2019).…”
Section: Estilo De Enseñanza Del Profesoradounclassified